The influence of non-active lockdowns on children’s motor development through SARS-CoV-2 pandemic - Camenidis, Carmen Magdalena; Baitel, Irina (Arena-Journal of Physical Activities, 2022)
While the SARS-CoV-2 pandemic took the whole world by surprise, humanity sought to organize itself in the fight against an unseen enemy by now. The school has moved into the online teaching system, and physical education classes have not been nearly what they used to be. Purpose: In this study, we tried to investigate how children’s motor development was influenced due to lack of physical activity because of school closure during the pandemic in order to know if it has influenced the weight of children by collecting data on body mass index (BMI). Methods: the anthropometric and motor capacity measurements; the method of comparing the results obtained with those of the National ‘Biomotric project’; the bibliographic studying; the data collection; the graphic representation and the data analysis and interpretation. The study subjects/participants were 119 boys and 85 girls aged between 7-14 years old. Results: We measured the motor development before the pandemic (AP), respectively February 2020, and during the pandemic (DP), respectively October 2020. The item categories represent the data collected from the motor tests applied to the children when they were physically present at schools, such as mobility, long jump from the spot, abdominal crunches, and speedrunning tests on the following distances: 25m for 1st grade, 30m for 2nd to 4th grade and 50 m for 5th to 8th grade. We chose to refer to the value of the median in order to eliminate, as much as possible, the influence of the extreme values recorded. Conclusions: There are minimal differences between the results obtained in the tests before the pandemic and those during the pandemic period. Although we would have expected the influence of non-active lockdown to be more significant than when schools were opened, in the sense of decreasing children’s motor skills, it can be seen that this was not the case for students from Maarif International Schools of Bucharest.